Early Health and School Outcomes for Children with Lesbian Parents: Evidence from Sweden - Lina Aldén; Anders Björklund; Mats Hammarstedt (Institute of Labor Economics (IZA), 2017)
Sweden was early to legalize same-sex partnership (1995), to allow same-sex couples to adopt children (2003), and to offer same-sex couples fertility treatment through the national health system (2005). Using population data, we identify children of lesbian parents as those whose biological mother was a registered same-sex partner no later than six months after the child's birth. The number of such children increased markedly from 1995 to 2010 with a total of 750 children for the whole period. We find that boys and girls with lesbian parents had 2.4 percent lower birth weight than other children, a difference that is statistically significant from zero at the 5 percent level. Girls, but not boys, also have a higher probability of having a low birth weight. We follow these children until age ten and observe diseases of the respiratory system. Boys with lesbian parents have a significantly lower probability of such diseases (-3.4 percentage points), and girls with lesbian parents an insignificantly higher probability (+2.4 percentage points). Our analysis of school outcomes at age ten uses a small sample so precision is low. The point estimates show that boys with lesbian parents outperform other children by around 10 percentiles higher test scores in Math and Swedish. These differences are barely significant, while estimates for girls are lower and not significant. For all outcomes, we find that children with lesbian parents benefit from their mother's socio-economic status, whereas they suffer in terms of birth weight from having been exposed to fertility treatment.
Keywords: I14; J12; J13; 330; lesbian parents; birth weight; early child outcomes